Condition inspection of rainwater tanks in Melbourne - Moglia, M.; Gan, K.; Delbridge, N.; Tjandraatmadja, G.; Gulizia, E.; Pollard, C.; Sharma, A.; Cook, Simon (2015)
© 2015, Engineers Australia. All rights reserved.The installation of rainwater tanks has increased to around 30% of homes in Melbourne largely from Government rebates over the Millennial Drought and introduction of 5-star home regulations in 2005. Rainwater tanks help to diversify a city's water supply and confer a range of environmental benefits, especially through reduction of stormwater runoff. However, the management of this infrastructure is left with home owners with little oversight from policy makers or water companies. As such, the longevity and efficacy of this investment over time is uncertain. Surveys of the physical condition of rainwater tanks will identify common faults and problems as well as quantify any deterioration over time. There has previously been no published large-scale study regarding the condition of rainwater tanks in Melbourne although a smaller study of limited scope has been reported for South East Queensland. This paper reports on the physical inspection of a sample of 417 sites with rainwater tank systems across Melbourne including the connected roof area, pumps and ancillary devices. The survey, undertaken in 2013 and 2014, shows that while some aspects are fairly non-problematic, such as those relating to the tank barrel, there are also some serious concerns. Too many foundations were found to be in a dangerous condition and faulty automatic switches and pumps contribute to a significant loss of water savings. There are also concerns about the water quality with more than half of all samples found to be either smelly and/or discoloured. The spread of arbovirus with mosquitoes breeding in tanks is another concern because many were found to contain mosquito larvae. The results have ramifications for Government and water company policies which are driving greater use of rainwater and highlight the need for improved management of these infrastructure assets.